Between Entertainment, Technology, Culture, and Business. The Syncretism of Media Discourse on Video Games in the Light of Genological Discourse Analysis - Kaszewski, Krzysztof (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2024)
The aim of the article is to demonstrate one of the fundamental characteristics of media discourse on video games: its syncretism. This pertains to the amalgamation of content and structures typical of several different spheres of human activity: entertainment, technology, culture, and business. A genre-based discourse analysis is employed to examine which genre patterns are typical of the media discourse on video games and the common methods of their manifestation. The paper discusses in greater detail four selected genres: video game review, news, overview, and a game publisher’s note. The research data was gathered from contemporary Polish-language media outlets specialised in gaming topics, as well as Polish online stores selling video games.